Ultra-high dose rate electron FLASH beam irradiation using a modified clinical linear accelerator - Gyu-Seok Cho; Kyo-Tae Kim; Soon-Sung Lee; Jeong-Hwan Kim; Dong-Han Lee; Hong-Suk Chang; Sang-Hyoun Choi; Kum-Bae Kim; Tae-Keun Yang; Dong-Hyun An; Geun-Beom Kim; Kun-Uk Kang; et al. (PLoS ONE, 2026)
FLASH radiation therapy reduced radiation-induced damage to normal tissue, compared to conventional radiation therapy, and active studies have been undertaken worldwide. While a number of preclinical studies have revealed the effectiveness of this novel radiotherapy, the biological effects have not been fully elucidated. Here, we implemented ultra-high dose-rate FLASH beam irradiation through machine modifications of the core components of an existing clinical linear accelerator, to build a database containing information related to the biological effects of the FLASH beam. We established a protocol that enables a quick conversion between the CONV and FLASH modes of an existing clinical linear accelerator. At 100 cm source-to-surface distance in 10 cm × 10 cm applicator conditions, we achieved FLASH electron beam irradiation characterized by 9.49 MeV mean energy, effective field size (95% iso-dose distribution) ∅ 39.9 mm, and maximum dose rate of 339.1 Gy/s. Irradiation of an elliptical Gaussian beam with flatness of 12.7% and symmetry of 0.3% was confirmed. Furthermore, most of the required preclinical conditions were satisfied. However, although the pulse dose value obtained from the protocol is expected to meet the requirement of 1 Gy/pulse, this result was not confirmed in this study, and further investigation is required.